Analisis Implementasi Regulasi Ekonomi Syariah dalam Fintech Syariah di Indonesia - Daffa Asysyakir; Syihabud Din; M. Akmal Khoirur Roziq; M. Farel Tsaqif; Iqbal Hilmawan; Muhamad Masrur (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2026)
Economic activity in society has been growing rapidly. This growth has been facilitated by the use of technology—known as fintech—making it an innovation that simplifies people’s lives. However, this development requires special attention from Islamic economic law. The aim is to ensure that the implementation of fintech remains in accordance with Sharia. However, the implementation currently lacks a strong foundation linking the mechanisms to existing regulations; therefore, this study focuses on aligning fintech mechanisms with the regulations formulated by the DSN-MUI in the form of fatwas. This study utilizes a qualitative approach with a literature review as its research method. It draws on scientific articles with relevant topics as its data sources. The results indicate a practical alignment between fintech models and DSN-MUI fatwas. This alignment enables Sharia contracts to serve as the foundation for fintech mechanisms. These findings can serve as a basis for further development of fintech to ensure it remains in harmony with Sharia economic law.